OPTIMALISASI POTENSI PESERTA DIDIK SMK AT-TAUFIQIYYAH MELALUI MANAJEMEN SDM DAN STRATEGI PEMASARAN KREATIF - Latif, Latif; Anwar, Rijatul; Susanto, Denies (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
SMK AT-Taufiqiyyah is one of the vocational education institutions that has great potential in producing graduates who are ready to work and entrepreneurship. However, in its implementation, a number of problems are still found. Some students have not been able to identify and develop their potential optimally, both in terms of skills, professional attitudes, and readiness to face the world of work. In addition, the lack of understanding of human resource management (HR) and effective marketing strategies is also an obstacle in increasing the competitiveness of graduates in the digital era. To overcome these problems, this community service activity is designed with an intensive training and mentoring-based approach. The solutions offered include: (1) HR management training which includes self-awareness recognition, time management, and soft skill improvement; (2) creative marketing strategy workshops that include branding, social media utilization, and digital marketing techniques; and (3) simulation of product/service-based entrepreneurship projects made by students. This activity is expected to develop an entrepreneurial mindset and increase the work readiness of students. The output targets of this activity include: (1) increasing students' understanding and skills in HR management and creative marketing; (2) the creation of at least 3 student business groups that practice the results of the training; (3) the preparation of training modules as continuous teaching materials in schools; and (4) publication of activities in the form of popular or scientific articles. By optimizing potential through this strategic approach, SMK AT-Taufiqiyyah is expected to be able to produce graduates who are not only technically skilled, but also adaptive and innovative in facing the challenges of the world of work and entrepreneurship.